Psychological basics of extracurricular activity organization in teaching Ukrainian language in the context of profession-oriented school education - Діденко, Наталія Миколаївна (Pedagogy of Higher and Secondary Education, 2015)
Didenko N. M. Psychological basics of extracurricular activity organization in teaching Ukrainian language in the context of profession-oriented school education. The article analyzes the age and individual characteristics of senior students of profession-oriented schools. The analysis of scientific papers of psychologists, psyholinguists, didactists on the problems of mental development and linguistic identity formation of high school students within extracurricular activities in Ukrainian language is carried out. Particular attention is paid to the theoretical aspects of basic cognitive mental processes of thinking, speech as the basics of human thinking, the structure of learning motivation, interest as a component of learning motivation.